Analgesic Activity of the Kappa Opioid Receptor Agonist - RU-1205 in Rats / Spasov AA ... [et al.] - AA, Spasov; OY, Grechko; DM, Shtareva; AI, Raschenko; NV, Eliseeva; VA, Anisimova (Universiti Teknologi MARA Cawangan Selangor, 2018)
Introduction: Opioid analgesics are the most efficient and widely used drugs for the management of moderate to severe pain. However, side effects associated with mu receptor activation, such as respiratory depression, tolerance and physical dependence severely limit their clinical application. Currently, the kappa-opioid system is the most attractive in terms of the clinical problem of pain, because kappa-agonists do not cause euphoria and physical dependence. The purpose of this study was to evaluate the antinociceptive effect of the novel compound - RU-1205. Methods: The analgesic activity of RU-1205 was studied on nociceptive models that characterize the central and peripheral pathways of pain sensitivity (hot plate test, electrically induced vocalisation, formalin test, writhing test). Results: RU1205 exhibited highly potent antinociceptive effects in rodent models of acute pain with ED50 values of 0.002 - 0.49 mg /kg. Pretreatment with the κ-opioid receptor antagonist nor Binaltorphimine significantly attenuated the analgesic activity of investigated substance in a hot plate test. Conclusions: It was established that the compound shows a significant dose-dependent central and peripheral analgesic effect. It was assumed kappa-opioidergic mechanism of analgesic effect of RU-1205.